Characteristics of punishment for property embezzlement and appropriation by military personnel through abuse of office - Sobko, Ganna; Chenshova, Natalia; Viunyk, Maksym; Duiunova, Tetiana; Palii, Evgenia (Legality : Jurnal Ilmiah Hukum, 2023)
The article is focused on the analysis of legislative regulation of sentencing and exemption from punishment of persons who have committed criminal offenses connected with the appropriation and embezzlement of military property by military personnel through the abuse of official position. The variability of responsibility for the appropriation and embezzlement of military property was analyzed, beginning with the Criminal Code of 1960, the effective Criminal Code of 2001, and the draft of new criminal legislation on this criminal offense. This study employed a comparative legal analysis of responsibility according to administrative and criminal legislation, defines the level of punishment for the committed offenses, and presents. The author’s classification of disciplinary, administrative, and criminal responsibility. Criminal offenses related to corruption were also analyzed and the restrictions that cannot be applied to persons who have committed corruption offenses were investigated. This study also proposes a list of corrupt criminal offenses, explores possibilities for mitigating criminal liability for persons who have committed corruption criminal offenses that would not exceed the ban on mitigating criminal responsibility for corruption offenses, and considers the possibility of imposing additional types of punishment to persons who have committed criminal offenses in the area of the appropriation and embezzlement of military property. Statistical data on administrative and criminal proceedings on this issue were analyzed.